2020
DOI: 10.1039/c9fo02922b
|View full text |Cite
|
Sign up to set email alerts
|

Study of viability of high pressure extract from pomegranate peel to improve carrot juice characteristics

Abstract: Extracts from fruit processing by-products usually present high amounts of bioactive compounds with several important activities such as antioxidant and antimicrobial capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
2
15
1
Order By: Relevance
“…Thus far, carrot has been used to produce blended beverages with high nutritional values, such as pineapple, orange, and carrot juice. Carrot juice has also been fortified with pomegranate peel extract, which increases the antimicrobial and antioxidant activity of the juice without altering its sensory features 49 . Carrot juice has also been combined with different fruit juices, for example, carrot‐grape juice, 6 carrot with mixed berry juice, 7 apple‐carrot juice, 8 carrot juice with orange peel and pulp extracts 9 and carrot juice with yoghurts 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, carrot has been used to produce blended beverages with high nutritional values, such as pineapple, orange, and carrot juice. Carrot juice has also been fortified with pomegranate peel extract, which increases the antimicrobial and antioxidant activity of the juice without altering its sensory features 49 . Carrot juice has also been combined with different fruit juices, for example, carrot‐grape juice, 6 carrot with mixed berry juice, 7 apple‐carrot juice, 8 carrot juice with orange peel and pulp extracts 9 and carrot juice with yoghurts 10…”
Section: Introductionmentioning
confidence: 99%
“…Carrot juice has also been fortified with pomegranate peel extract, which increases the antimicrobial and antioxidant activity of the juice without altering its sensory features. 49 Carrot juice has also been combined with different fruit juices, for example, carrotgrape juice, 6 carrot with mixed berry juice, 7 apple-carrot juice, 8 carrot juice with orange peel and pulp extracts 9 and carrot juice with yoghurts. 10 In the present study, 12 colored carrot juices obtained from different carrot varieties were compared in terms of their content of bioactive compounds and health benefits; moreover, finding the most attractive carrot juice with high health-promoting activity and elevated product quality will help the fruit and vegetable industry to use the data for evaluating food materials as food ingredients and for creating novel food products to attract the interest of children.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, at the end of storage, the color parameters faded (data not shown), but the addition of PP extract mitigates the color reduction, and that is clear in Figure 7 , where color change (ΔE) value was observed as limiting the color change in PP-supplemented smoothies; the ΔE value in the control was 6.14; however, in PP-SYS4, it decreased by 22%. Trigo et al [ 81 ] found that with the addition of pomegranate peel extract to carrot beverage, the whiteness was not affected by PPE, but heat treatment led to higher L * levels compared to the HPP treatment. The increase in L * values was noticed in the first week of storage, but the L* remained constant within the next few days.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, studies testing the antibacterial activity of pomegranates almost exclusively used solvent extracts, including methanol extracts of fruit rind; chloroform‐ethanol and water extracts of fruit pericarp (Voravuthikunchai et al., 2005); methanol (Reddy et al., 2007) and ethanol (Cristani et al., 2007) extracts of pomegranate peel; and acetone, methanol, ethanol and water extracts from fruit leaves, roots and bark (Mathabe et al., 2006). These extracts are not desirable and generally toxic as supplements for humans, although high‐pressure extraction methodologies seem to produce non‐toxic extracts (Trigo et al., 2020). We suggest that microencapsulation would allow for the storage and delivery of active compounds without the need for undesirable solvents.…”
Section: Resultsmentioning
confidence: 99%